The role of the geographical textbooks in grounding negative stereotypes of a tourism destination: The case of Upper Silesian conurbation in Poland - Mariusz Szubert; Michał Żemła (Administrative Sciences, 2019)
Tourists' decisions on selecting their destinations are driven by their imagination of available offers, rather than by the real offers. The special role of the image of tourism destination in the process of building a competitive position result, among other things, comes from the fact the image is a factor of competitiveness influenced by both intentional and accidental actions of entities, whom are active in a particular tourism destination as well as environmental elements, which are beyond the influence of these entities. The cities of the Upper Silesian Conurbation were for many years perceived as completely dominated by heavy industry. Nowadays, after significant changes in their economy and environment, local authorities are struggling to fight that negative perception. The aim of the paper is to examine if the negative image of the Conurbation is grounded by the textbooks for geography for secondary schools in Poland. The textbooks were studied using the content analysis as an example of important autonomous sources of information. Particular stress was put on analysis of the heading and pictures in the chapters on the Conurbation. The results prove that industrial image of the region is being grounded by the geography textbooks. It was discovered that the picture of Upper Silesian Conurbation that might be found in researched textbooks is almost identical with what was previously presented in the literature as tourists' perception of the Conurbation. The results prove the role of the textbooks and the whole school education as factors shaping the image of particular places that people have also as adults. That role was neither researched nor clearly stated in the literature so far.
Keywords: 350; destination image; negative stereotypes; post-industrial cities development; Upper Silesian Conurbation